Mengoptimalkan Penjualan Dengan Memanfaatkan Pemasaran Digital Yang Efektif Pada Cv.Ageng Store - Miftahul Ulum; Mochamad Ismail Sanjaya; Santi Pertiwi Hari Sandi (Peneliti.net, 2023)
This visit aims to analyze and implement effective digital marketing strategies to increase sales at CV. Agent's shop. CV. Ageng Store is a retail company operating in the fashion industry. In today's digital era, digital marketing has become a key factor in achieving marketing and sales success. The method used in this research is a case study that involves analyzing the current situation and developing an effective digital marketing strategy for CV. Agent's shop. During the situation analysis stage, market research and competitor analysis are conducted to understand consumer trends, preferences, and marketing practices by competitors in the fashion industry. In addition, internal company data is also analyzed to identify current strengths and weaknesses in marketing and sales. The results of the situation analysis show that CV. Ageng Store can take advantage of digital marketing to increase online presence, increase interaction with customers, and expand market reach. By using social media as a platform to interact with customers, CV. Ageng Store can increase engagement and build closer relationships with customers